A clinical case of acute meningoencephalitis of tuberculosis etiology and pneumocystis pneumonia in an HIV-infected patient - Halahan, Anastasiia; Khmelnytska, Veronika (The Ukrainian Scientific Medical Youth Journal, 2025)
this article describes a clinical case of severe tuberculosis meningoencephalitis and Pneumocystis pneumonia in an HIV-infected patient who was treated in the infectious disease intensive care unit of the "St. Michael’s Clinical Hospital" in Kyiv. According to medical records, pulmonary tuberculosis was first diagnosed in 2018, with a recurrence in 2022 affecting the Th9-Th10 thoracic spine. The patient completed a full course of anti-tuberculosis therapy. Since 2019, he had been on antiretroviral therapy, with undetectable viral load and target CD4+ cell levels achieved. The aim of this study is to emphasize the importance of monitoring HIV-infected patients to prevent and control complications. The uniqueness of this case lies in the presence of cognitive impairment along with focal neurological symptoms, the development of respiratory failure due to Pneumocystis pneumonia, and the rapid regression of clinical manifestations with positive laboratory dynamics following treatment initiation. Despite the patient’s good adherence to therapy, opportunistic infections can still worsen the course of the underlying disease if CD4+ lymphocyte count drop below 350 cells/mm³.